2017
DOI: 10.1021/acs.macromol.7b00249
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Ion Transport and Self-Assembly of Polymer Electrolytes via End-Group Chemistry

Abstract: We report a rational design of solid-state dry polymer electrolytes with high conductivity, high mechanical strength, and improved cation transference number. Thiol–ene click chemistry provided orthogonal control over the type and number of end groups in poly­(styrene-b-ethylene oxide) (PS-b-PEO) block copolymers. This approach permitted the synthesis of PEO chains with reduced crystallinity, reminiscent of PEO oligomers, thereby playing a key role in improving the room temperature conductivity. Intriguingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 47 publications
1
63
0
Order By: Relevance
“…81 Further small improvements to the mechanical properties as well as the conductivity can be achieved through bi-continuous morphologies such as gyroid, which can be accessed through end-group modification for low molecular weight systems. [82][83] Similar studies on multivalent salts in BCPs have not been performed but would provide interesting comparisons in their effect on ionic conductivity and mechanical property retention as compared with lithium counterparts.…”
Section: Mechanical Property Control In Multivalent Ion Conductorsmentioning
confidence: 99%
“…81 Further small improvements to the mechanical properties as well as the conductivity can be achieved through bi-continuous morphologies such as gyroid, which can be accessed through end-group modification for low molecular weight systems. [82][83] Similar studies on multivalent salts in BCPs have not been performed but would provide interesting comparisons in their effect on ionic conductivity and mechanical property retention as compared with lithium counterparts.…”
Section: Mechanical Property Control In Multivalent Ion Conductorsmentioning
confidence: 99%
“…As an alternative, poly(ethylene oxide) (PEO)‐based electrolytes have been studied for decades because PEO electrolytes exhibit higher lithium‐ionic conductivities than other polymer electrolytes . However, despite the research efforts in this area, the reported conductivities are typically in the range of 10 −7 to 10 −4 S cm −1 at room temperature and the mechanical properties are sensitive to temperature, making these electrolytes unsuitable for practical applications. Therefore, most polymer electrolytes that have shown success in battery tests are so‐called gel polymer electrolytes, which contain excessive amounts of liquid additives .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, PEO is highly crystalline, and research shows that crystallinity inhibits the flow of Li + ions . BCPs are advantageous because the second block adds strength to the membrane, the BCP morphology can help direct ion flow and the second block can inhibit PEO crystallization . In BCPs, the salt concentration influences the morphology by changing the apparent volume fraction for the conductive block.…”
Section: Applications Of Crystallizable Block Copolymersmentioning
confidence: 99%
“…However, PEO crystallinity remained the same. In another study, the PEO end‐group chemistry in PS‐ b ‐PEO copolymer was altered between single or double carboxylic acid or hydroxyl groups . It was shown that the weaker primary alcohol association with Li + and a designed diol end‐group were both more favorable to improve conductivity in the PEO phase.…”
Section: Applications Of Crystallizable Block Copolymersmentioning
confidence: 99%